An Insight into Educational Data Mining - Kaur, Balwinder; Gupta, Anu; Singla, RK (International Journal of Computer Sciences and Engineering, 2019)
Education lays foundation for the development of the country. Enhancements in the educational technologies has improved educational process. Educational institutes are now capable to store large volumes of data related to student admissions, course attendance, examination results and so forth which need to be analysed for the progress of institutes. Data mining provides techniques to explore educational data. Educational Data Mining (EDM) is such an emerging multidisciplinary research field which deals with developing methods to explore the educational data to gain knowledge. The knowledge gained can be used to improve teaching- learning process and decision making process of higher educational institutes. It also helps in detecting student behaviour and their learning outcomes which can be used for their future betterment. This paper puts forth an effort to study EDM, its environment and components including tools and techniques used. It also gives an insight into the Education Data Mining process of knowledge discovery. The present study also puts forth challenges involved in EDM which represents opportunities for future research work to be carried out.